Step-by-step explanation:
The mean is the average. Add up all the points, then divide by the number of points.
(12 + 17 + 11 + 13 + 17 + 15) / 6 = 14⅙
Problem 11
<h3>Answer: h =
2A/b</h3>
------------------
Explanation:
We need to get h by itself. To do so, we first multiply both sides by 2. Then we divide both sides by b
A = (1/2)*b*h
2A = b*h
b*h = 2A
h = 2A/b
================================================
Problem 12
<h3>Answers:</h3>
- Equation: (n+2)/5 = 14
- Solution to that equation: n = 68
------------------
Explanation:
The number n is increased by 2 to get n+2
Then we divide by 5 to get (n+2)/5
This is set equal to 14 to get the equation (n+2)/5 = 14
Solving the equation would look like this
(n+2)/5 = 14
n+2 = 5*14 .... multiply both sides by 5
n+2 = 70
n = 70-2 .... subtract 2 from both sides
n = 68
================================================
Problem 13
<h3>Answer: Not a solution</h3>
------------------
Explanation:
We'll replace every copy of x with -3 and simplify
-2x + 5 > 13
-2*(-3) + 5 > 13
6 + 5 > 13
11 > 13
The last inequality is false because 11 is not greater than 13. Since the last inequality is false, this makes the first inequality false when x = -3.
Therefore, x = -3 is not a solution.
Answer:
1 2/6 is the correct answer
Step-by-step explanation:
in 2 1/6 + -5/6 what you do is you can turn the plus sign into a minus sign and make -5/6 5/6 so now the problem is 2 1/6 - 5/6 and the awnser to that is 1 2/6
X^2/(x- 9 = 81/(x - 9)
This is the equation for which you want the solution.
Multiplying both sides of the equation by (x - 9) we get
x^2(x - 9)/(x - 9) = 81(x - 9)/(x - 9)
So the (x - 9) goes out from both the denominator and the numerator and then the simplified equation becomes
x^2 = 81
x ^2 = (9)^2
x = 9
So the value of the unknown variable x comes out to be 9.